Major Prophets' Difficulties in the Old Testament - Jean Damascene ngendahayo (SAGACITY : Journal of Theology and Christian Education, 2022)
The purpose of this paper was to go through the purpose of God's call to the selected Prophets' lives and challenges when speaking to the world on His behalf. A prophet's role in the Old Testament was to speak God's word. Some would predict events, heal people, and/or perform miracles. Moses is an Old Testament prophet who predicted the arrival of another prophet. That Prophet is Jesus. God understood the dangers of men ruling over men and the root of the problem. This study clearly recounts the lives and challenges that the Major Prophets faced, as well as how they were able to come up with their missions with the help of God. So, the five books of The Major Prophets (Isaiah, Jeremiah, Lamentations, Ezekiel, and Daniel) cover a significant time span and present a diverse range of messages. Isaiah, for example, spoke to the nation of Judah about 150 years before their exile into Babylonia and urged them to be faithful to God. By sampling, this study mainly discussed the two Prophets, Jeremiah and Daniel, based on their long call and the hardships they faced when delivering God's message to the respective place to which God sent them. This study primarily discussed the two Prophets, Jeremiah and Daniel, based on their long call and the hardships they faced when delivering God's message to the respective place to which God sent them. Jeremiah preached a message of God's judgment against the rulers and people of Judah for violating the nation's religious and legal traditions, but Hananiah opposed him, preaching a message of peace and salvation and foretelling the deliverance of the Israelite nation from the hands of their enemies. Jeremiah cried out to those same people on the verge of exile, pleading with them to repent. Jeremiah's Lamentations is a dirge written during Judah's exile. Ezekiel and Daniel, the last two Major Prophets, spoke and wrote to the exiles, encouraging them to remember that God was still in control and would eventually restore the spiritual fortunes of His disciplined nation. Daniel was first and foremost a God's servant, a prophet who demonstrated to God's people how to live a holy life. The significance of this study is to help readers understand the life and long history of the Prophets, as well as their patience and faithfulness to the Almighty Heavenly God.